Variaciones del índice de cono en suelo movilizado posterior al tráfico de un tractor equipado con dos tipos de neumáticos y a cuatro velocidades de desplazamiento - Gabriel Filho, A.; Lanças, Kleber Pereira [UNESP]; Bonnin, J. J. [UNESP]; Leite, F. [UNESP]; Paula, C. A. [UNESP]; Monteiro, L. A. [UNESP] (My University, 2007)
The tractor is one of the machines that more traffics over the soil during the processes involving agricultural production. The interaction tractor/soil is made by the tires which, in most of the cases, are pneumatic. The tire type and the tractor travel speed, interfere directly on the pressure over the soil. One of the techniques employed to evaluate the alterations that tractor traffic causes in the soil is to measure its Cone Index. The aim of this research was to evaluate the same Cone Index alterations caused by an agricultural tractor equipped with both radial tires and bias ply tires, trafficking mobilized soil in four different travel speeds. The experiment was performed in a LATOSSOLO VERMELHO, located 22°51' S, 48°25'W and 770 m of altitude, in Botucatu-SP, Brazil. The soil mobilization was performed with a chisel plow and a disc arrow. The traction was accomplished with a John Deere tractor, model 6600, with 88 kW of power and 6,723 kg. Equipment requiring a force of 25kN was traced by the tractor draw bar. The experimental design was in randomized blocks with 4 × 2 factorial arrangements, with two distinct treatments corresponding to the types of tires (bias and radial) and the four travel speeds, with six replications. There were selected the following speeds: 3.5, 3.9, 5.1 and 5.9 km h-1. To determine the soil resistance, there was utilized MSSU - Mobile Soil Sampling Unit, with which the Cone Index was obtained in layers from 0-100, 100-200, 200-300, 300-400, 400-500 and over 500 mm deep. The Cone Index where evaluated in areas with non contact between tire and soil (ICn) and in the tire footprint track (ICp). There were calculated the Cone Index increments caused by the tractor tire (AIC) and the results showed that as the tractor travel speed increased, there were observed decrements in the medium values of cone index. The radial tire provided smaller values of the Cone Index in the superficial layer of the soil (0 to 100 mm) in relation to the bias ply tire, when the speed was approximately 6 km h-1. The increment in the Cone Index, promoted by the tractor, was more intense in the first 200 mm depth, but it also reached the layer from 200 to 300 mm.
The Cone Index in soil mobilized after tractor traffic with bia-ply and radial tires and in four forward speeds
Keywords: Agricultural mechanization; Soil compaction; Tire test; agricultural production; agricultural soil; compaction; soil mechanics